Stationary Probability Distributions of a Markov Chain - B. SETIAWATY (MILANG Journal of Mathematics and Its Applications, 2002)
This article shows that stationary probability distributions of a Markov chain can be classified into two classes. These classes are determined by the type of communicating classes of the chain.